Avaliação da terapia fotodinâmica antimicrobiana em Aggregatibacter actinomycetemcomitans mediada por azul de metileno em veículo surfactante - Anselmo, Giuliana Giovinazzo (2020)
Periodontal disease is a public health problem and has a higher incidence in the adult population, which can lead to loss of teeth. Its treatment is the elimination of pathogens present in the periodontal pocket. Antimicrobial photodynamic therapy (aPDT) has been studied as an aid in this treatment, but in the oral environment, the photochemical effects encounter challenges such as dimming the photosensitizer (FS). The use of sodium dodecyl sulfate (SDS) produces the chemical breakdown of FS and has been shown as an alternative to PDT. The aim of this study was to investigate the effect of aPDT mediated by methylene blue (AM) on a periodontal pathogen in a vehicle with SDS. The behavior of aPDT mediated by methylene blue (AM) in phosphate buffered solution (PBS) and 0.25% surfactant vehicle (SDS) was evaluated. For this purpose, inoculum of pure strain of A. actinomycetemcomitans ATCC 29523 was grown from stocks in brain and heart infusion agar (BHI) at 37 ° C in a microaerophilic environment. The aPDT was performed with a diode laser (Photon Lase III, DMC, São Carlos, Brazil) with a wavelength of 660 nm, output power of 100 mW, well irradiation of 250 mW / cm2, energy of 6.18 and 30 J corresponding to the times of 60, 180 and 300s and radiant exposure of 15, 45, 75 J / cm2, respectively. Microbial death was evaluated by counting colony-forming units (CFU); the incorporation of FS by the bacteria was evaluated by optical absorption spectroscopy of the supernatant; as well as the morphology of microorganisms was investigated by scanning electron microscopy (SEM). The results indicated that aPDT with AM in PBS reduced 4.8 logs of bacterial death, however, the association with SDS reduced the effect of aPDT considerably, by 1.45 logs. The presence of 0.25% SDS in this bacterium caused an 80% reduction in the incorporation of AM, and the SEM images indicate that clusters of extracellular substances are formed in contact with SDS. It was concluded that aPDT in 0.25% SDS was ineffective in A. actinomycetemcomitans; the same in contact with this periodontopathogen, prevented the entry of FS in the bacteria.